Fim da delegação constitucional em matéria previdenciária: racionalização com a competência unificada na Justiça Federal - Arapiraca, Ciro José de Andrade (2017)
This study intends to demonstrate that the Brazil’s Constitution has amid its own rules an obstacle to the achievement of the reasonable duration of trials’ principle. Although the delegation of federal jurisdiction to state courts lawsuits related to social security matters was considered relevant at a certain historical moment, the expansion of federal courts’ structure occurred, coupled with its interiorization’s process as well as other external factors, have shown that some changes must be done in such judicial proceedings to enable for timely and effective judicial provision. It will be tried to demonstrate that an important step to reach the mentioned goal will necessarily pass through the abrogation of state courts jurisdiction’s delegation. Indeed, prior to propose any change to the Brazilian legal system is a mandatory requirement to inquire on the possibility of altering or suppressing part of the Constitution’s original text, which was created at the time of the promulgation of the Brazil’s Constitution of 1988. As suggested in title of this academic work, a reliable solution to the presented issue would be the rationalization of the social security jurisdiction through the transference of all cases and the related competence solely to federal courts. Considering that there is no reason to adopt an abrupt changing process to reach the above-mentioned solution, this study will build an architected and gradual approach. Therefore, the called fundamental social rights and the principle of the reasonable duration of proceedings, the boundaries of the Federal State (Federalism), the history development of federal justice in Brazil and abroad will be analyzed. Additionally, the jurisdiction of Brazilian federal courts will be assessed to seek answers to the main question raised during the current work, regarding the existing statistical data on social security lawsuits, class’ theory and their respective logical operations